High-volume endurance exercise training stimulates hematopoiesis by increasing ACE NH2-terminal activity. Issue 20 (29th October 2021) - Magalhães, Flávio de Castro; Fernandes, Tiago; Bassaneze, Vinícius; Mattos, Katt Coelho; Schettert, Isolmar; Marques, Fabio Luiz Navarro; Krieger, José Eduardo; Nava, Roberto; Barauna, Valério Garrone; Menezes de Oliveira, Edilamar
Abstract: One of the health benefits of endurance exercise training (ET) is the stimulation of hematopoiesis. However, the mechanisms underlying ET-induced hematopoietic adaptations are understudied. N–Acetyl–Seryl–Aspartyl–Lysyl–Proline (Ac-SDKP) inhibits proliferation of early hematopoietic progenitor cells. The angiotensin I-converting enzyme (ACE) NH2 -terminal promotes hematopoiesis by inhibiting the anti-hematopoietic effect of Ac-SDKP. Here we demonstrate for the first time the role of ACE NH2 -terminal in ET-induced hematopoietic adaptations. Wistar rats were subjected to 10 weeks of moderate-(T1) and high-(T2) volume swimming-training. Although both protocols induced classical ET-associated adaptations, only T2 increased plasma ACE NH2 -domain activity (by 40%, P =0.0003) and reduced Ac-SDKP levels (by 50%, P <0.0001). T2 increased the number of hematopoietic stem cells (HSCs; ∼200%, P =0.0008), early erythroid progenitor colonies (∼300%, P <0.0001) and reticulocytes (∼500%, P =0.0007), and reduced erythrocyte lifespan (∼50%, P =0.022). Following, Wistar rats were subjected to T2 or T2 combined with ACE NH2 -terminal inhibition (captopril (Cap) treatment: 10 mg.kg −1 .day −1 ). T2 combined with ACE NH2 -terminal inhibition prevented Ac-SDKP decrease and attenuated ET-induced hematopoietic adaptations. Altogether, our findings show that ET-induced hematopoiesis was at least partially associated with increased ACE NH2 -terminal activity and reduction in the hematopoietic inhibitor Ac-SDKP.